The Effect of Modified and Unmodified Exercises on Motor Ability on Passing Ability of the Junior High School Volleyball Team Negeri 23 Kerinci - Ifan Wahyu Saputra; Umar Umar; Masrun Masrun; Yuni Astuti Astuti (JETL (Journal of Education, Teaching and Learning), 2025)
Overhead passing is a fundamental skill in volleyball that significantly influences game performance. Modified ball training is often used to enhance players' motor skills, but its effectiveness compared to non-modified training remains underexplored. This study aims to analyze the effect of modified and non-modified training on motor skills and its impact on overhead passing ability in the volleyball team of SMP Negeri 23 Kerinci. The study employs a quantitative experimental design with 16 volleyball players divided into two groups: modified ball training and non-modified training. Normality was tested using the Shapiro-Wilk test, and since the data were not normally distributed, the Mann-Whitney test and multiple linear regression were used for statistical analysis. The results indicate that modified ball training significantly improves overhead passing ability compared to non-modified training (p = 0.014). Players with higher motor skills showed greater improvement than those with lower motor skills. Regression analysis revealed that motor skills positively influence overhead passing (β = 0.506, p = 0.009), while modified training has a negative but significant effect (β = -0.564, p = 0.005), suggesting its effectiveness for players with higher motor skills. Coaches are encouraged to implement modified training to enhance volleyball players' technical skills.